Injection Technologies for the Repair of Damaged Concrete Structures - Panasyuk, V.V. (Springer Netherlands : Imprint: Springer, 2014)
This book analyzes the most important achievements in science and engineering practice concerning operational factors that cause damage to concrete and reinforced concrete structures. It includes methods for assessing their strength and service life, especially those that are based on modern concepts of the fracture mechanics of materials. It also includes basic approaches to the prediction of the remaining service life for long-term operational structures. Much attention is paid to injection technologies for restoring the serviceability of damaged concrete and reinforced concrete structures. In particular, technologies for remedying holes, cracks, corrosion damages etc. The books contains sample cases in which the above technologies have been used to restore structural integrity and extend the reliable service life of concrete and reinforced concrete constructions, especially NPPs, underground railways, bridges, seaports and historical relics.